Formulation of nanocream whitening preparation from a combination of yam starch (Pachyrhizus erosus L.) and rice starch (Oryza sativa L.) - Nur, Hijrotun; Dalimunthe, Gabena Indrayani; Rani, Zulmai; Yuniarti, Rafita (Journal of Pharmaceutical and Sciences, 2024)
Whitening cosmetics have become a popular choice in modern society, with the perception that beauty is associated with white skin. The high market demand is an opportunity for cosmetic business actors but it also increases the risk of illegal cosmetic production containing hazardous materials such as hydroquinone. One of the cosmetic ingredients that is often found in whitening creams containing hydroquinone, which is effective in removing dark spots, has the risk of serious side effects. Therefore, it is advisable to find a safe, natural alternative for long-term skin whitening. Jicama starch and rice water starch are natural choices for whitening cosmetics. Nanoparticle-based cosmetics are superior to micro-scale cosmetics. The objective of the research was to determine whether a combination of jicama starch and rice water starch whitening cream can meet the characteristic requirements of a nano cream, to determine all concentrations of jicama starch and rice water starch whitening nano cream that meet the physical quality requirements and to determine all concentrations of jicama starch and rice water starch whitening nano cream have different effectiveness. This research method was True Experimental with Post Test Only Control Group Design research design. The independent variables are variations in the concentration of yam starch and rice water starch. The dependent variables were sample characteristics, characteristics of the whitening nano cream formulation and nano cream effectiveness test. The results showed that yam starch and rice water starch had effectiveness as whitener with a concentration of f3 (5:5) water content of 55.67%, sebum of 16% and pigment of 15.67%. The whitening cream met the characteristics of a nano cream with particle sizes of f0: 134.04, f1: 1849.20, f2: 147.64 and f3: 188.14 nm. Yam starch and rice water starch in the preparation of the whitening nano cream meet the physical quality requirements.